The Use of Smartphones and the Reformulation of Family Relations - Pinto , Mariana (2022)
The relationship between the smarthphone and family members is perceived when we observe presence and influence of this technology in their lives. Not only in their behavior as individuals but also in the type of relationship they build with their households. Whether due to easy access or quick communication, the arrangement of these connections reflects people's ways of living and coexistence, resulting in a new structure. These interactions often combine digital environments and real activities, producing moments of communication between online media and life in their physical spaces, where children, parents, grandparents, and their smartphones often travel together. Therefore, this exploratory study aims to understand how family relationships are established from the digital experiences of individuals with smartphones, starting from how family dynamics are reorganized in the face of this individual and community usability. It is structured based on a literature review, then its methodology (developed by qualitative research using a semi-structured script) and ending with a cross-sectional analysis of the data collected from each interviewed family, which allows us to compare perspectives. Therefore, it is willing to bring a new observation, from the smartphone as a constant technological innovation, capable of leading a new configuration about the dynamics of family members, their roles, and limits, modifying the format of relationship and interaction, whether with each other or with the world outside home.